2005
DOI: 10.1016/j.otohns.2004.09.092
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngologic presentations of amyotrophic lateral sclerosis

Abstract: C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 14 publications
(33 reference statements)
4
64
0
1
Order By: Relevance
“…Muscle weakness can be present with UMN and with LMN involvement. Regardless of the type of dysarthria, identifiable changes to speech are expected in over 90% of PALS as the disease progresses (Chen & Garrett, 2005). Speech intelligibility is reduced, and 80% or more of PALS may ultimately need an alternative communication method to function in daily activities (Beukelman, Fager, & Nordness, 2011).…”
mentioning
confidence: 99%
“…Muscle weakness can be present with UMN and with LMN involvement. Regardless of the type of dysarthria, identifiable changes to speech are expected in over 90% of PALS as the disease progresses (Chen & Garrett, 2005). Speech intelligibility is reduced, and 80% or more of PALS may ultimately need an alternative communication method to function in daily activities (Beukelman, Fager, & Nordness, 2011).…”
mentioning
confidence: 99%
“…17 However, "quivering" of the arytenoids and/or TVFs has not been previously reported. In this study, quivering of the arytenoids and/or TVFs was observed in 8/12 MND subjects.…”
Section: Other Laryngeal Observationsmentioning
confidence: 96%
“…16 Variability has also been noted in patterns of abnormal TVF movements, with the following patterns reported: incomplete adduction, bowing, hyperfunction, and reduced abduction. 17 Laryngospasm and glottic narrowing have also been reported in bulbar ALS.…”
Section: Dystussia In Motor Neuron Disease (Mnd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 85% of individuals with ALS experience dysphagia, or swallowing impairment, leading to malnutrition, dehydration, aspiration, pneumonia, reduced psychosocial health, and morbidity 2, 3. Progressive rigidity and weakness of the diaphragm, internal intercostals and abdominal muscles also contribute to impairments in the ability to generate adequate subglottic air pressure to produce a protective and effective cough 4, 5.…”
Section: Introductionmentioning
confidence: 99%